ANALISIS CURAH HUJAN PENYEBAB BANJIR BESAR DI JAKARTA PADA AWAL FEBRUARI 2007 - Nugroho, Sutopo Purwo (Jurnal Air Indonesia, 2008)
Flood that has occured in Jakarta in 27 January - 2 February 2002 was a result of heavy rain and impact of over discharge streams within its catchment area. Furthermore, occurence of low air pressure around northern Australia and Intertropical Convergence Zone (ITCZ) around Java Sea up to Banda Sea, has driven moists in the Asia into the area. Precipitation resulting flood is a return period about 1 to 1000. In Ciliwung watershed, mean rainfall of 142,5 mm/day and return period of about 100 years. This was bigger than mean rainfall during the period of 29 January 2002 about 110 mm/day that return period 200 years.Ã‚Â Katakunci : hujan, banjir, periode ulang.